Plum spooky - Evanovich, Janet (New York : St. Martin's Press, 2009)
Wulf Grimoire can kill without remorse and disappear like smoke. He's chosen Martin Munch as his new business partner, and he's chosenTrenton, New Jersey, as his new playground. It's up to Plum and Diesel, a bounty hunter, to hunt down Munch and Grimoire.
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women bounty hunters -- Fiction; New Jersey -- Fiction; Mystery fiction; Humorous fiction